Small Animal Veterinarians' Communication With Dog Owners From a Motivational Interviewing Perspective - Enlund, Karolina Brunius; Jennolf, Ebba; Pettersson, Ann (Frontiers in Veterinary Science, 2021)
Veterinary communication skills are fundamentally important in animal practice. Despite client-centered communication being recommended as the optimal medical communication style, a paternalistic approach is still common in veterinary medical encounters with pet owners. Motivational interviewing (MI) is such a client-centered, evidence-based counselling method aiming to strengthen a person’s motivation and commitment to behavior changes. In this exploratory study, the aim was to investigate Swedish small animal veterinarians’ use of client centered communication with dog owners regarding dental home care in dogs. This was achieved by analyzing the use of MI-techniques among veterinarians without previous training or knowledge of the method. Individual telephone calls, reflecting a veterinary clinical scenario, between small animal veterinarians (n=8) and a trained professional actor playing a dog owner were recorded and coded according to a MI coding protocol (MITI 4.2.1). In the present study, the degree of spontaneously used MI was low. From a MI-communication perspective, with a simulated dog owner, the veterinarians predominantly relied on asking questions, giving information and persuasive talk. The veterinarians dominated the conversations and made minimal attempts to involve the dog owner resulting in a power imbalance between veterinarian and client. As the degree of spontaneously used MI was found to be low, MI-training may be required in order to apply the method in professional counselling. The veterinarians’ communication pattern suggested a paternalistic communication style, when attempting to motivate a client to brush his/her dog’s teeth. We suggest that Motivational Interviewing (MI) has a potential to improve veterinary communication and adherence to medical recommendations if introduced and implemented in veterinary practice.